Comportamiento de ventas en el local “La Reina del Repuesto” en la ciudad de Babahoyo, periodo 2022. - Gavidia Mancilla, Sandra Viviana (2023)
Sales is the success of a company and business that not only has to do with the financial situation, but also takes into consideration different aspects involved in the whole process. Now, the sales behavior has to do with the constant change of the sales index, evaluating the sales behavior it is possible to compare sales of two different periods of time in order to know if the sales strategies are giving the expected results or if it is necessary to rethink some of them. In view of this, the main objective of this case study is to propose innovative strategies that guarantee sales during the next quarters of the store "La Reina del Repuesto in the city of Babahoyo" period 2023, analyzing the sales behavior and the other micro problems found in the analysis of the store's situation. This was achieved through methodological tools such as surveys, interviews and direct observation of the local reality. The conclusion is that the sales index of the store during the first quarter of the year 2022 is much higher than the first quarter of the year 2023, this is due to poor customer service, competitiveness and costs not in line with the quality of the product offered. In the same way, it is observed that the store does not have a sales plan nor does it apply competitiveness or sales strategies appropriate to its needs, which results in low profitability for the store La Reina del repuesto.